2015
DOI: 10.1007/s40291-015-0175-y
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/AKT Pathway and Its Mediators in Thyroid Carcinomas

Abstract: Thyroid malignancies are the most common endocrine system carcinomas, with four histopathological forms. The phosphoinositide 3-kinase-protein kinase B/AKT (PI3K-PKB/AKT) pathway is one of the most critical molecular signaling pathways implicated in key cellular processes. Its continuous activation by several aberrant receptor tyrosine kinases (RTKs) and genetic mutations in its downstream effectors result in high cell proliferation in a broad number of cancers, including thyroid carcinomas. In this review art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 117 publications
5
56
0
Order By: Relevance
“…BDNF can also bind to its major receptor, tropomyosin-related receptor kinase B (TrkB), leading to the activations of multiple downstream signal pathways, such as PI3K/AKT, RAS/ERK, PLC/PKC, AMPK/ACC, and JAK/STAT pathways [29], which promote tumorigenesis. Specifically, PI3K/AKT pathway has been widely reported to be involved in thyroid cancer progression and development [30, 31]. Several miRNAs, such as miR-107 [32], miR-15a-5p [33], miR-204 [34], and miR-206 [35], inhibit cancer progression by suppressing BDNF.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF can also bind to its major receptor, tropomyosin-related receptor kinase B (TrkB), leading to the activations of multiple downstream signal pathways, such as PI3K/AKT, RAS/ERK, PLC/PKC, AMPK/ACC, and JAK/STAT pathways [29], which promote tumorigenesis. Specifically, PI3K/AKT pathway has been widely reported to be involved in thyroid cancer progression and development [30, 31]. Several miRNAs, such as miR-107 [32], miR-15a-5p [33], miR-204 [34], and miR-206 [35], inhibit cancer progression by suppressing BDNF.…”
Section: Discussionmentioning
confidence: 99%
“…22 Moreover, studies have revealed that phosphoinositide 3-kinase AKT (PI3K-AKT) pathway also drived carcinogenesis of PTC. 23 Cell proliferation plays an important role in tumor progression and prognosis. Activation of PI3K-AKT signaling pathway results in high cell proliferation and vascularity.…”
Section: Introductionmentioning
confidence: 99%
“…Among the other altered signal transduction pathways, the FoxO and PI3K-Akt signaling pathway is known to be involved in thyroid cancer (Zaballos & Santisteban 2013, Gunda et al 2014, Sun et al 2015, Nozhat & Hedayati 2016. However, previous high frequency genetic studies have reported the activation of somatic alterations of genes encoding effectors in the MAPK signaling pathway, including point mutations in…”
Section: :10mentioning
confidence: 99%